'The antithesis of the film magnate': Irving Thalberg and the politics of ethno-religious identity in early Hollywood*. Issue 1 (3rd May 2016) - Feeley, Kathleen A.
Abstract: As a powerful, high-profile member of Los Angeles' Jewish and German-American communities and a founder of MGM, the native-born, middle-class Irving Thalberg was framed as a 'better, finer' Jew as compared to his older, immigrant, US film industry mentors. This essay sheds new light on Thalberg's hybrid identity as German-Jewish-American, asking how it shaped his life, work, popular persona, and memory. As MGM production chief, Thalberg's work included shaping culture and philanthropy in 1920s and 1930s Los Angeles. Then and now, Thalberg as 'model minority' both challenged and reinforced pernicious ethno-religious stereotypes that undergirded myths of Jewish media domination in an industrializing America.